Corrosion mechanisms in model binary metallic glass coatings on mild steel and correlation with electron work function. (October 2022) - Mahajan, Chaitanya; Hasannaeimi, Vahid; Pole, Mayur; Kautz, Elizabeth; Gwalani, Bharat; Mukherjee, Sundeep
Abstract: Effect of chemistry change on corrosion mechanisms and passive film characteristics of model Ni-P and Co-P metallic glass coatings on mild steel was studied because of their simple chemistry and widespread use. Increase in phosphorus content led to improved corrosion resistance. Results indicated the presence of hypophosphite and phosphate anions on the corroded surfaces. Enrichment of phosphorus in the passive layer was observed, which likely promoted the restoration of the protective hypophosphite anion layer during dissolution. A correlation between electronic structure and corrosion resistance was established, with relative work function increasing with increase in phosphorus content. Highlights: Effect of chemistry change on the corrosion behavior of model metallic glass coatings on Mild Steel in NaCl electrolyte. Corrosion resistance increased with increase in phosphorus content: M90 P10 85 P15 80 P20 (M = Ni, Co). X-ray Photoelectron Spectroscopy revealed the presence of elemental P, hypophosphite, and phosphate layers after corrosion. Atom Probe Tomography revealed enrichment of phosphorus at the passive layer/base alloy interface. Scanning Kelvin Probe potential increased with increase in phosphorus in both systems.